2010
DOI: 10.1016/j.jsams.2009.07.004
|View full text |Cite
|
Sign up to set email alerts
|

MCT1 genetic polymorphism influence in high intensity circuit training: A pilot study

Abstract: Monocarboxylate Transporter 1 (MCTl) mediates the transport of the main fraction of lactate across the sarcolemma. A common polymorphic MCTl variant has been identified, but its role in high intensity exercise performance has not been defined. We investigated the influence of MCTl A1470T polymorphism (rsl049434) on lactate accumulation after high intensity circuit training. Ten men aged 20-26 performed three controlled circuit training (CWT) sessions at 60%, 70%, and 80% of the 15 repetition maximum (15 RM), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
2
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 26 publications
4
68
2
5
Order By: Relevance
“…Although the molecular and cellular functions of these SNPs have not yet been evaluated, in silico analysis found that rs4485435 in MCT1 gene leads to a D490E variation in the amino acid sequence, while rs60844753 and rs995343 may affect the binding of transcription factors to the promoter of MCT1 and MCT2 genes, respectively, leading to the expression variations of mRNAs. One previous study has observed the influence of rs1049434 genotypes on lactate transport across sarcolemma in males (Cupeiro et al 2012), and another study has demonstrated that the carriers of T genotype in rs1049434 exhibit a poor lactate transport capacity (Cupeiro et al 2010), which is in line with the notion that elevated lactate transport facilitates the proliferation of cancer cells and thus contributes to the poor prognosis of cancer patients (Pertega-Gomes and Baltazar 2014; Pertega-Gomes et al 2014). However, further functional investigation on these SNPs is needed to elucidate their effects on gene expression, lactate transfer activity as well as cell survival in CRC.…”
Section: Discussionmentioning
confidence: 59%
“…Although the molecular and cellular functions of these SNPs have not yet been evaluated, in silico analysis found that rs4485435 in MCT1 gene leads to a D490E variation in the amino acid sequence, while rs60844753 and rs995343 may affect the binding of transcription factors to the promoter of MCT1 and MCT2 genes, respectively, leading to the expression variations of mRNAs. One previous study has observed the influence of rs1049434 genotypes on lactate transport across sarcolemma in males (Cupeiro et al 2012), and another study has demonstrated that the carriers of T genotype in rs1049434 exhibit a poor lactate transport capacity (Cupeiro et al 2010), which is in line with the notion that elevated lactate transport facilitates the proliferation of cancer cells and thus contributes to the poor prognosis of cancer patients (Pertega-Gomes and Baltazar 2014; Pertega-Gomes et al 2014). However, further functional investigation on these SNPs is needed to elucidate their effects on gene expression, lactate transfer activity as well as cell survival in CRC.…”
Section: Discussionmentioning
confidence: 59%
“…Individuals with mutant T allele had lactate transport rates 60-65% lesser of mean normal. Recently, Cupeiro et al [111] have examined the influence of the MCT1 Glu490Asp polymorphism on lactate accumulation after training. Male carriers of the MCT1 490Asp (T) allele showed higher lactate accumulations than noncarriers during circuit weight training.…”
Section: Mct1 (Slc16a1) Rs1049434 a Allelementioning
confidence: 99%
“…One of those (SNP ID: rs1049434) is associated with a reduced lactate transport activity in red blood cells (RBCs) and higher than normal accumulation of lactate in blood during exercise (Cupeiro et al, 2010;Merezhinskaya et al, 2000). SNPs have been found also in the coding sequence of the equine MCT1 and CD147, but they were at different locations to those found in humans and were not associated with the lactate transport activity (Mykkänen et al, 2010b;Reeben et al, 2006).…”
Section: Introductionmentioning
confidence: 99%